2011
DOI: 10.1002/ijc.26401
|View full text |Cite
|
Sign up to set email alerts
|

The novel indole compound SK228 induces apoptosis and FAK/Paxillin disruption in tumor cell lines and inhibits growth of tumor graft in the nude mouse

Abstract: Drugs in clinical use with indole structure exhibit side effects. Therefore, to search for indole compounds with more efficacy and less side effect for cancer therapy, we developed a novel indole compound SK228 and examined its effects and mechanisms on antitumor growth and invasion inhibition in cell and tumor xenografts in nude mice models. SK228 significantly inhibited growth of different lung and esophageal cancer cell lines at sub-micromolar range, but not normal lung cells. SK228 induced DNA damages main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
1
19
1
Order By: Relevance
“…Increasing evidence suggested that mitochondria are the critical source of ROS and could be considered as a potential target in cancer therapy. Many naturally-derived compounds were found to effect mitochondrial activity, such as curcumin, colchicine, paclitaxel and vinca alkaloid-derivative SK228 [ 33 , 34 , 35 , 36 ]. Alternations in the mitochondrial functions via the increase of ROS generation and disruption of mitochondrial membrane potential can lead to cell death [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggested that mitochondria are the critical source of ROS and could be considered as a potential target in cancer therapy. Many naturally-derived compounds were found to effect mitochondrial activity, such as curcumin, colchicine, paclitaxel and vinca alkaloid-derivative SK228 [ 33 , 34 , 35 , 36 ]. Alternations in the mitochondrial functions via the increase of ROS generation and disruption of mitochondrial membrane potential can lead to cell death [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, inhibition of paxillin phosphorylation by the sialytransferase inhibitor Lith-O-Asp or other small molecules suppress lung tumor progression and metastasis (Chen et al, 2011;Huang et al, 2012), as well as breast cancer progression (Golubovskaya et al, 2008), in vivo. Interestingly, these molecules affect phosphorylation activity in the N-terminal region of paxillin, and we have shown here and in a previous study that the expression of the N-terminal alone substantially increases migration when transfected into paxillin knockdown cells, where N-terminus and C-terminus of paxillin have been shown to have complementary but opposite effects on cell migration and invasion (Sero et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier investigation, we showed that tetraindole (1,4-bis{di[1 H -indol-3-yl]methyl}benzene) and its 5-hydroxy tetraindole derivative, SK228, which contains a benzene core structure with four appended hydroxyindole groups, induce G2 arrest and apoptosis in human breast adenocarcinoma (MCF 7 and MDA-MB-231) cells through externalization of membrane phosphatidylserine, DNA fragmentation, and activation of caspase-3 [19]. In addition, it also has been shown that SK228 treatment causes a marked inhibition of the growth of an A549 tumor cell xenograft without producing adverse effects on liver and kidney function of treated mice [20].…”
Section: Introductionmentioning
confidence: 99%